A survey of East Palaearctic Lycosidae (Araneae). 11. Two new genera from the Acantholycosa complex - Marusik, Yuri M.; Omelko, Mikhail M.; Koponen, Seppo (Zootaxa, 2015)
Two new genera of wolf spiders belonging to Pardosinae, Gulocosa gen. n. and Melecosa gen. n., are erected to accommodate Gulocosa eskovi sp. n. (♂ ♀, Khabarovsk Province, Russia) and Sibirocosa alpina Marusik, Azarkina & Koponen, 2004, respectively. A new combination was also established: Melecosa alpina (Marusik, Azarkina & Koponen, 2004) comb. n. (ex. Sibirocosa). Polytomous and dichotomous keys are provided for the Palearctic Pardosinae genera.